The Impact of Logistics Service Quality in Online Food Delivery Applications (OFDAs) on the Satisfaction of Student Consumers in Ho Chi Minh City - Do, Doan Binh; Huynh, Thanh Loc; Mai, Chi Thien; Nguyen, Huynh Truc Anh; Hoang, Thi Thanh Tuyen; Bui, Thi Bich Lien (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2026)
The paper investigates the factors constituting logistics services quality in Online food delivery applications and the satisfaction of student consumers in Ho Chi Minh City, Vietnam in order to pinpoint areas for improvement and allocate resources effectively. Particularly, the factors Discrepancy Handling, Delivery Cost, Information Quality, Delivery Time, Delivery Reliability and Personnel Contact are identified as components of logistics service. The final results demonstrate that all six variables are significant antecedents to Customer Satisfaction.